English Consonant Mispronunciation by Jakarta International University's Final Year English Department Students - Joy Ivana Yagi; Maria Dewi Rosari (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2023)
Understanding how to produce and how to use speech sounds are essential for English learners to avoid mispronunciation. However, most of the English learners would then likely to mispronounce the English consonants that can lead to misunderstanding, miscommunication and even negative expression. This study attempts to find out the mispronounced English consonants and the most commonly mispronounced English consonants by final year English Department students of Jakarta International University. Qualitative descriptive was used in this research with a pronunciation test as the research instrument. In discovering the data, the researchers listened to the audio recording from the participants and transcribed the pronounced English words containing English consonants into IPA symbol systems. The result of this study shows that there are 12 English consonants mispronounced by the 10 students and four of them became the most frequently mispronounced consonants. This study is beneficial for the lecturers and students as a heads-up in being aware of English consonant sounds that tend to be mispronounced even by final year English Department students. This research is also expected to be a reference for future research to fill in the gaps in the research field of English mispronunciation.